Síndrome metabólico en un grupo de adultos mayores no institucionalizados según criterios de organismos internacionales (2016)
ABSTRACT: Although metabolic syndrome is common in elderly people, it is not clear if cardiovascular risk is increased in this population group. Objective: To determine the proportion of metabolic syndrome in a group of elderly people older than 60 years according to international organizations criteria. Materials and methods: Cross sectional descriptive study performed in 141 adults older than 60 years in Medellin-Colombia. The metabolic syndrome was classified according to the Third Report of the National Cholesterol Education Program (NCEP ATP III) and the International Diabetes Federation (IDF) criteria. Socio-demographic, anthropometric, clinical, biochemical and life-style variables were assessed Results: Were female 73.8 % of individuals and 84.4 % had ages between 60-74 years old. The metabolic syndrome was diagnosed in 45.4 % of the population based on the IDF criteria and 27.0 % according to ATPIII. Abdominal obesity, low HDL cholesterol and hypertriglyceridemia were the most frequent components found. The metabolic syndrome based on IDF criteria was more frequent in women (p= 0,026), in elderly people with low educational level (p=0,011), and with higher BMI (p <0,001). Conclusion: The proportion of MS was high according to IDF criteria; In addition, association with female gender, level of education and BMI was found.